Semiotic in Interpreting the Text of Women's Role Indonesian Horror Film in "Setan Jamu Gendong" - Rr. Astri Indriana Octavita; Yulia Sofiani Zaimar (Journal of English Language and Culture, 2018)
This research applies an analysis of a woman character in Indonesian horror film, through deeply exploration of Setan Jamu Gendong movie. This horror film, that is concerned with female sexuality. Jamu seller character in Setan Jamu Gendong movie would be chosen to be the subject of this academic research, usually comparing their features with those of the stereotype. The data that is taken, show the jamu seller should be considered as protagonist characters. Nevertheless, she could express multiple functions. While this is a broad and concentrate on area of the research, work in it has been shaped by a pronounced emphasis upon semiotic and feminist theory, which the researchers think, has limited the field in analyzing. In defining these diverse constructs, the researchers expand this focus sexuality by drawing from critical theories of semiology to provide the details of the way that taken-for-granted ideas about normative female sexuality are articulated, and stereotyping in popular culture. Over the research, it would show, how these paradigms serve to constrain and simplify broader cultural conceptualizations of female semiotically sexuality, placed them in second gender, At the outset of the research, the researchers had hoped to find out, that the horror genre in Indonesia was a place in which alternative modes of being and subordination could be explored and considered.Keywords: women, jamu, semiotic, gender, stereotype